The Influence of Self-Adjustment on Social Interaction of 4-5 Years Children - Widyanoor, Christ Junearna; Sugiyo Pranoto, Yuli Kurniawati (BELIA: Early Childhood Education Papers, 2019)
The ability to interact socially is one aspect of the characteristics of growth and development. The inhibition of the self-adjustment process can interfere with the child’s social interaction process. Social interactions that do not meet social expectations will endanger social acceptance by the group. This will eliminate the opportunity for children to learn socially. The absence of adjustments between parties who interact also makes the process of social interaction disrupted and can be stopped. This study aims to determine the effect of the adjustment on the social interaction of children in TK Pertiwi 2 Serang. This research is quantitative with the method of Simple Linear Regression Analysis. The population of the study is all children aged 4-5 years in Serang Village with a sample of 38 children. The sampling technique is Purposive Sample, which is the determination of samples with certain considerations. The research data are obtained through validity and reliability tests of 41 items and 0.937 for the adjustment scale and 39 items and 0.950 for the scale of social interaction. Based on the results of Simple Linear Regression analysis, a correlation value of 0.804 is obtained. It means the relationship between the variables of self-adjustment and social interaction is high. The coefficient of determination is 64.7%, rounded up to 65% positive effect, meaning that the better the child’s adjustment, the better the social interaction. While 35% are other factors that are not examined. The calculation results obtained by the regression equation Y = 21.121 + 0.765X. The equation corresponds to a simple linear regression formula, Y = a + bX, where Y is the dependent variable, a constant, b regression coefficient, and X independent variable.